Ophthalmology Medical Negligence Cases Decided by NCDRC: Retrospective Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
In the present scenario, medical negligence has become a serious issue in India and many a times it has led to litigations in consumer courts and/or in civil or criminal courts. The present study’s focus is to highlight the pattern and causes of medical negligence in cases related to ophthalmology speciality decided by the National Consumer Dispute Redressal Commission (NCDRC) and give an insight into pattern of compensation awarded by the NCDRC.The NCDRC decided 942 cases of alleged medical negligence cases of all specialties from year 2002 to February 2018. Out of these 942 judgments, 30 judgments of alleged medical negligence cases related to ophthalmology specialty from year 2002 to February 2018 were collected for the present study. Out of 30 cases, in 22 cases (73.3%) medical negligence was proved. Majority of cases (66.6%) were diagnosed with suffering from cataract followed by glaucoma (10%). In 16 cases (53.33%), information regarding medical negligence at stages of patient was not available while in 11 cases (36.67%) deficiency of service was present at post operative stage. Highest compensation claimed was Rs.1 Crore while lowest claimed compensation was Rs 2 Lac. Highest awarded compensation was 6 Lac while lowest awarded compensation was 25,000. Average compensation claimed and awarded was Rs 2,426,969.00 and Rs 21,4000.00, respectively. Due to increasing awareness among consumer regarding their rights, there are rising trend of complaints filed in various courts for alleged medical negligence which has resulted in doctors to go towards defensive medicine. This could be detrimental to the society in long run. Therefore, there is necessity to make balance between patient’s right and professional honesty and sovereignty. Outcome of this study will help in improving the quality of healthcare and trust and transparency in doctor–patient relationship which ultimately will benefit the society.
Keywords: Medical negligence; NCDRC; Compensation; Ophthalmology; Consumer protection act